Marek’s disease herpesvirus serotype 1 in broiler breeder and layer chickens in Malaysia - Othman, Iryanti (Vet World, 2019)
AIM: This study aimed to investigate the occurrence of Marek’s disease (MD) in five poultry farms in Malaysia using postmortem examination, histopathology, and polymerase chain reaction (PCR). MATERIALS AND METHODS: Tissue samples were collected from 24 broiler breeder chickens from four commercial broiler breeder farms and six layer chickens from one layer farm. Gross and histopathological examinations and PCR amplification of the gene encoding for avian MD herpesvirus (MDV-1) were conducted. RESULTS: Gross pathological changes including hepatomegaly, splenomegaly, lymphomatous lesion at the mesentery, oviduct atrophy, and follicular atresia with lymphomatous were observed, whereas diffuse multifocal whitish infiltration of the spleen, neoplastic infiltration in the liver, intrafollicular lymphoid infiltration of the bursa of Fabricius, and lymphomatous tumor at the mesentery were seen on histopathological examinations. Confirmation by PCR showed that a total of 16 (53.33%) samples were positive for avian MDV-1. Although the outbreak involved a much larger number of birds in the respective farms, our investigation was limited based on resource and time frame allocated for the study. CONCLUSION: The findings from this study help in emphasizing the potential threats of MDV to the poultry industry globally, in general, and in Malaysia, in particular. As the scope of the current study is limited, future studies focusing on MDV pathogenesis, typing, and causes of vaccine failures are recommended.